2021
DOI: 10.1016/j.brs.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Parsing the antidepressant effects of non-invasive brain stimulation and pharmacotherapy: A symptom clustering approach on ELECT-TDCS

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Goerigk et al [83] randomized patients with major depressive disorder into an escitalopram group, a tDCS group, and a placebo group. In that study, tDCS was applied by placing the anode on L-DLPFC and by placing the cathode on R-DLPFC at 2 mA for 22 sessions.…”
Section: Psychiatric Disoredersmentioning
confidence: 99%
“…Goerigk et al [83] randomized patients with major depressive disorder into an escitalopram group, a tDCS group, and a placebo group. In that study, tDCS was applied by placing the anode on L-DLPFC and by placing the cathode on R-DLPFC at 2 mA for 22 sessions.…”
Section: Psychiatric Disoredersmentioning
confidence: 99%
“… 12 Studies of differential symptom cluster response to brain stimulation including electroconvulsive therapy and transcranial direct current stimulation have also found that the core mood and dysphoric symptoms respond better to treatment than other symptom clusters. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that core mood and dysphoric symptoms exhibit more favourable responses to treatment than other symptom clusters. In other words, interventions targeting brain regions associated with mood and dysphoria have demonstrated superior outcomes compared to addressing other symptom domains (Goerigk et al, 2021;Wade et al, 2020). Therefore, by employing total depression scores to assess treatment response, the ability to detect different responses among individual symptom clusters may be compromised (Fried & Nesse, 2015).…”
Section: Baseline Biomarkers and Association With Response To Tbs Tre...mentioning
confidence: 99%